MULTI-CRITERIA DECISION MAKING USING THE WASPAS METHOD FOR ONLINE ENGLISH COURSE SELECTION - Nurdiana Handayani; Nofitri Heriyani; Fajar Septian; Allan Desi Alexander (Jurnal Teknoinfo, 2023)
English is an international language used in communication between countries. For this reason, the ability to speak English is of added value in entering the world of work. Because of how important English is, currently many course institutions offer English courses including online learning. With so many online English courses, it requires carefulness in choosing the right course and according to your needs. To find an online English course, you need to know one by one in advance about the programs and facilities offered. This study aims to implement the Multi-Criteria Decision Making (MCDM) approach with Weighted Aggregated Sum Product Assessment (WASPAS) in a decision support system for selecting online courses. The WASPAS method is used as a multi-criteria settlement model that can minimize errors and maximize the assessment for selecting the highest or lowest scores. Based on case studies conducted using the WASPAS method in decision making, it shows that the alternative with the highest score was obtained by the British Council (A5) with a value of 0.8927, followed by English Today (A2) with a value of 0.8311, Education First (A1) with a value of 0.8302, IELC English Campus (A4) with a score of 0.7859 and Engoo English Course (A3) with a score of 0.7823. In addition, the test results from black-box testing have a value of 100%, which means the system can work as it should.